FOETAL HYDROCEPHALUS IN A JERSEY CROSSBRED COW:CASE REPORT - Shukla, BP; Verma, SK; Parihar, AS; Singh, Shivendra (Indian Journal of Veterinary Sciences and Biotechnology, 2014)
Bovine congenital anomalies are infrequent occurrence believed to be induced by various environmental and genetic factors. Various congenital anomalies like monsters (Fazili, 2012), meningocele (Purohit et al., 2012), atresia ani (Purohit et al., 2006) etc are reported in bovines. Hydrocephalus is due to an abnormal accumulation of fluid in the cranial cavity. Internal hydrocephalus is due to excessive fluid in the ventricular system. External hydrocephalus is rare and due to excessive fluid between the brain and dura mater. Internal and External hydrocephalus may be combined (Roberts, 1971).